Reflections On the Formation and Distribution of Wealth – Part I - Turgot, Anne Marie Jacques (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
The author sustains, in forty-nine arguments, that it is impossible to create wealth in the presence of redistributive policies, using the land factor as the main theme of his analysis. He defends free trade and property rights, and shows how voluntary exchanges and the division of labor, with the consequent generation of wealth, arise exactly from the unequal distribution of land.